2022
DOI: 10.1186/s12936-022-04325-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum interleukin-1β levels as a potential indicator for malarial infection and severe malaria: a meta-analysis

Abstract: Background Interleukin (IL)-1β is a proinflammatory cytokine that has a role in disease-related inflammation, including malaria. However, reports on the effect of IL-1β on malaria severity are inconsistent. Therefore, meta-analyses to compare differences in IL-1β levels between patients with severe malaria, patients with uncomplicated malaria and healthy controls were performed. Methods The PRISMA standards were used to perform a systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…A recent meta-analysis showed that serum IL1β levels are higher in patients with severe malaria than in patients with uncomplicated malaria. However, the level in patients with uncomplicated malaria was very similar to that of healthy controls (Mahittikorn et al, 2022). This observation fits very well with the results presented here.…”
Section: Discussionsupporting
confidence: 92%
“…A recent meta-analysis showed that serum IL1β levels are higher in patients with severe malaria than in patients with uncomplicated malaria. However, the level in patients with uncomplicated malaria was very similar to that of healthy controls (Mahittikorn et al, 2022). This observation fits very well with the results presented here.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement, we observed that even though there was no significant difference in the pro-inflammatory levels between the SM and UM, the levels in the SM group seem to increase as that of the UM group decrease especially with IL-1β. These results are in line with several other observations that pro-inflammatory cytokines promote inflammation and tissue damage, which may imply that their levels correlate with malaria disease severity and death [ 11 , 14 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that co-infection triggered immune suppression in our study which is consistent with the idea that co-infection can lead to immune exhaustion, where the immune system is unable to effectively respond to one or both of the pathogens. Interleukin (IL)-1β as a pro-inflammatory cytokine has a role in disease-related inflammation, including malaria and typhoid fever (32). However, reports on the effect of IL-1β on malaria severity are inconsistent.…”
Section: Discussionmentioning
confidence: 99%